2023
DOI: 10.3390/audiolres13040042
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Hearing Preservation Surgery in Small Vestibular Schwannoma

Abstract: Objective: to evaluate recent contributions to the literature on prognostic factors of hearing preservation in small vestibular schwannoma microsurgery. Methods: review of the most recent studies. Results: factors such as tumor size, preoperative hearing status, tumor growth rate, tumor origin, surgical approach, radiological characteristics, results of preoperative neurophysiological tests, preoperative symptoms and demographic features have been investigated and some of them reported to be significant in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…This might happen due to the close adhesion of the tumor to the vital auditory structures like the cochlear nerve during operation [ 29 , 30 ]. Other studies have suggested that the surgical technique can preserve hearing function, especially in smaller tumors [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might happen due to the close adhesion of the tumor to the vital auditory structures like the cochlear nerve during operation [ 29 , 30 ]. Other studies have suggested that the surgical technique can preserve hearing function, especially in smaller tumors [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The discussion about the optimal approach for microsurgery of small T1/T2 VS without contact to the brainstem (Koos [ 9 ] grading system: T1 = intracanalicular, T2 = with extrameatal extent but without contact to the brainstem) is still controversial. The functional outcomes and complications of both the MCF and RS approaches are comparable and mostly dependent on the expertise of the center or surgeon [ 10 ]. Middle fossa surgery involves elevating the temporal lobe with a retractor to access the petrous bone and the IAC from superior.…”
Section: Introductionmentioning
confidence: 99%